SAST & AHP in Determining The Best Strategy of Office Ergonomics Program Improvement to Prevent Risk of Musculoskeletal Disorders At XYZ Company Qatar - Wiguna, Gun Gun; Darkun, Kholil; Sulistyadi, Kohar (ADI Journal on Recent Innovation, 2020)
Ergonomics Program has been recommended by many studies as one of the main guidelines in equipping employees at work to prevent injuries and health problems. One of the main benefits gained from implementing the Ergonomics Program is that it reduces the risk of injury by adapting work that suit to human, not forcing human to adapt to work. Offices that are designed using ergonomic principles can improve performance and reduce workplace injuries such as musculoskeletal disorders (MSDs). This study aims to obtain strategies of Office Ergonomics Program Improvement to prevent risk of musculoskeletal disorders (MSDs) cases in XYZ Company Qatar. The research approach was conducted through qualitative descriptive using expert based approach (System of System Methodology - SoSM). The study began by analyzing data on MSDs cases and sick leave related to MSDs. The results of analysis are taken into consideration when collecting assumptions for office ergonomics program improvement and its level of importance and certainty. The method used is Strategic Assumption Surfacing and Testing (SAST). Prioritizing of strategic assumptions are determined using Analytic Hierarchy Process (AHP) method. The data obtained were analyzed using Software Expert Choice 11. The results of analysis showed that Policy and procedure had the greatest value with 0.256, while the work station was 0.219, health check-up 0.059, awareness program 0.087, regular exercise 0.202, training 0.088 and supervision / monitoring 0.089.